1994
DOI: 10.1007/bf00398051
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin predicts progression to diabetes mellitus in Pima Indians with impaired glucose tolerance

Abstract: Summary Glycated haemoglobin could offer several practical advantages over the OGTT for assessing glucose metabolism. Initial cross-sectional studies (1983)(1984)(1985) on 381 subjects (mostly Pima Indians) described the relationship between HbAlc (a specific glycated Hb) and the OGTT. We performed follow-up OGTTs and HbA~c measurements on 257 of these same subjects 1.6-6.1 years later. Subjects were again grouped according to both the result of the OGTT (normal, IGT or diabetes, by WHO criteria) and HbA~ resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that circulating HbA1c levels are associated with the conversion of pre-diabetic phase into clinical diabetes [35][36][37][38]. Further, a strong association between baseline HbA1c and incidence of type 2 diabetes was also suggested in a large-scale prospective study among middle aged women [39].…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that circulating HbA1c levels are associated with the conversion of pre-diabetic phase into clinical diabetes [35][36][37][38]. Further, a strong association between baseline HbA1c and incidence of type 2 diabetes was also suggested in a large-scale prospective study among middle aged women [39].…”
Section: Discussionmentioning
confidence: 79%
“…Progression rates for isolated IGT were similar to those for isolated IFG and progression rates for the combined IFG and IGT group were higher in each observation period. Fewer determinants of progression were identified in the IGT group than in population-based studies, where most consistently the following were identified: higher levels of blood glucose (HbA 1c , FBG, 2hBG), obesity (BMI and WHR), known hypertension and ethnicity [12,13,15]. However, the Hoorn study only found 2hBG and fasting proinsulin to be predictors of progression [14].…”
Section: Discussionmentioning
confidence: 99%
“…By knowing which risk factors or changes in risk factor levels determine progression to diabetes, we may be able to develop individualised focused interventions. Current publications on determinants of progression from IGT have studied population-based cohorts including moderate and low-risk individuals; few studies have reported on IFG [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…BMI was 29.5 kg/m 2 . 42 In a study by Little et al (1994) 45 in Pima Indians, 39% progressed from IGT to diabetes after a mean follow-up of 3.3 years, but the proportion developing diabetes was much higher in those with a raised baseline HbA 1c level (13 out of 19; 68%) than in those with a normal baseline HbA 1c level (13 out of 47; 28%). The upper limit of normal HbA 1c level was taken to be 6%.…”
Section: Definitionsmentioning
confidence: 99%